Cluster head based routing algorithms and performance study for ad hoc wireless networks - Pang, Kong Ling (2008)
Mobile Ad Hoc Network (MANET) is a multi-hop wireless network of mobile nodes without any fixed infrastructure. In the absence of dedicated routers, every node contributes towards the configuration and maintenance of the routing framework. Routing protocols need to consider inter-related factors like node mobility, bandwidth scarcity and energy constraints. This project will study the performance of hierarchical routing protocols as compared to flat routing protocols. Secondly, to introduce a more efficient and effective hierarchical algorithm for MANET, which is called Fault-tolerance Cluster Head based (FTCH) routing protocol.